Access to Employment and Property Values in Mexico - Atuesta, Laura H.; Ibarra-Olivo, J. Eduardo; Lozano-Gracia, Nancy; Deichmann, Uwe (World Bank, Washington, DC, 2018)
Location is one of the main characteristics households consider when buying a property or deciding where to live, since it determines accessibility to employment subcenters and public transport stations. Using a geographically-referenced data set on new housing developments, this paper estimates how households value accessibility in Mexico City. The results are shown considering road accessibility to formal employment subcenters (private accessibility) and distance to the main public transport stations in the city (public accessibility). The results suggest that accessibility to employment subcenters is considered an amenity for households, while being closer to a Metro station is perceived as a dis-amenity. Moreover, households located in neighborhoods with a greater proportion of informal workers and lower education levels give a lower value to private accessibility than households located in neighborhoods with a lower proportion of informal workers or in high-educated neighborhoods. These results are evidence of the existence of spatial segregation in the city, where disadvantaged households are segregated not only because of their economic conditions, but also because they are located farther away from employment opportunities.